Global, regional and national burden of inflammatory bowel disease in females from 1990 to 2021: an analysis of the global burden of disease study 2021 - Peng, Jingyi; Yuan, Yuan; Zhang, Jie; Ding, Yang; He, Xingxing (Frontiers in Global Women's Health, 2025)
Background & aimsThe global incidence of inflammatory bowel disease (IBD) has markedly increased over past several decades. Gender-specific differences have been observed in the epidemiology, manifestation, and prognosis of IBD. Given these distinctions, a focused analysis of the latest epidemiological trends in female patients is essential for advancing targeted healthcare.MethodsA comprehensive analysis of IBD incidence, mortality, and disability-adjusted life years (DALYs) in females was performed using data from the Global Burden of Disease (GBD) study from 1990 to 2021, with stratifications by age, region, country, and sociodemographic index (SDI).ResultsIn 2021, approximately 187,134 females were diagnosed with IBD globally. Incidence rates were highest among females aged 30–60, with disease burden increasing significantly with age in older populations. Geographically, High-Income North America had the highest IBD burden in females in 2021, while Australasia experienced the most significant increase from 1990 to 2021 (estimated average percentage changes (EAPC) = 1.13, 95% CI 0.8–1.46). Nationally, 75 countries and territories showed upward trends in the age-standardized DALYs (disability-adjusted life years) rate (ASDR), with the steepest rise observed in Mauritius (EAPC = 2.28, 95% CI 0.82–3.76). DALYs due to IBD in females also increased across all SDI regions, showing a positive correlation between SDI and ASDR.ConclusionsThe global burden of IBD in females has significantly risen from 1990 to 2021, with marked age, regional and SDI-based differences. Incidence rates are higher in high-income regions in Europe and North America, with the sharpest increases observed in East Asia, highlighting the need for age and region-specific IBD management strategies.